Small RNA F6 Provides Mycobacterium smegmatis Entry into Dormancy - Artem Grigorov (MDPI AG, 2021)
Regulatory small non-coding RNAs play a significant role in bacterial adaptation to changing environmental conditions. Various stresses such as hypoxia and nutrient starvation cause a reduction in the metabolic activity of Mycobacterium smegmatis, leading to entry into dormancy. We investigated the functional role of F6, a small RNA of M. smegmatis, and constructed an F6 deletion strain of M. smegmatis. Using the RNA-seq approach, we demonstrated that gene expression changes that accompany F6 deletion contributed to bacterial resistance against oxidative stress. We also found that F6 directly interacted with 5′-UTR of MSMEG_4640 mRNA encoding RpfE2, a resuscitation-promoting factor, which led to the downregulation of RpfE2 expression. The F6 deletion strain was characterized by the reduced ability to enter into dormancy (non-culturability) in the potassium deficiency model compared to the wild-type strain, indicating that F6 significantly contributes to bacterial adaptation to non-optimal growth conditions.